2017
DOI: 10.1016/j.jcte.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D but not dietary vitamin D intake is associated with hemoglobin in women of reproductive age in rural northern Vietnam

Abstract: Background and objectivesHypovitaminosis D and anemia are both prevalent in Vietnam, and low vitamin D status may be a risk factor for anemia. This study aimed to 1) describe vitamin D intake and its determinants, and 2) examine the associations of vitamin D intake and serum 25(OH)D concentrations with hemoglobin and anemia.Methods and study designWe used data from the baseline survey of a pre-conceptual micronutrient supplementation trial in women of reproductive age (WRA) in Thai Nguyen, Vietnam (N = 4961). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Furthermore, it was difficult to replace vitamin D content of food based on the food composition databases from other countries due to the vast difference of food (containing vitamin D) among Chinese people, especially commercial food and fortified food. In general, the main source of vitamin D is the synthesis mediated by UVB radiation and dietary vitamin D intake may not be a good proxy for vitamin D status [71,72]. Thus, we were more inclined to use serum 25-hydroxyvitamin D to assess vitamin D status.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, it was difficult to replace vitamin D content of food based on the food composition databases from other countries due to the vast difference of food (containing vitamin D) among Chinese people, especially commercial food and fortified food. In general, the main source of vitamin D is the synthesis mediated by UVB radiation and dietary vitamin D intake may not be a good proxy for vitamin D status [71,72]. Thus, we were more inclined to use serum 25-hydroxyvitamin D to assess vitamin D status.…”
Section: Limitationsmentioning
confidence: 99%
“…Vitamin D deficiency and anemia frequently coexist [1,2,3,4,5]. A number of mechanisms could explain this association [1] and recent data provide evidence for a direct role of vitamin D in the suppression of hepcidin: the primary regulator of systemic iron homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple clinical studies detected a similar association where Michalski et al (32) found low vitamin D status may be linked to reduced HC in pregnant women. Also, Yuan et al (33) reported that maternal serum 25OH-VD < 50.0 nmol/L may be a risk factor for gestational anemia, and it should be monitored for the high-risk pregnant women.…”
Section: Results:-mentioning
confidence: 64%